1986
DOI: 10.1083/jcb.102.5.1878
|View full text |Cite
|
Sign up to set email alerts
|

The organic matrix of the skeletal spicule of sea urchin embryos.

Abstract: Abstract. The micromeres that arise at the fourth cell division in developing sea urchin embryos give rise to primary mesenchyme, which in turn differentiates and produces calcareous endoskeletal spicules. These spicules have been isolated and purified from pluteus larvae by washing in combinations of ionic and nonionic detergents followed by brief exposure to sodium hypochlorite. The spicules may be demineralized and the integral matrix dissolves. The matrix is composed of a limited number of glycoproteins ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
65
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(68 citation statements)
references
References 32 publications
(42 reference statements)
3
65
0
Order By: Relevance
“…A starting point is at the differentiation gene batteries that generate the biomineral matrix. Earlier evidence indicated that many specific protein components of the biomineral matrix are present in both demineralized embryonic skeletal spicules and demineralized adult endoskeleton, i.e., spines and test plates (9). Analysis of biomineralization genes in the S. purpuratus genome sequence (10) proves this is the case, although, for some families of these genes, certain paralogues are used in adult skeletons, some in embryonic and some in both.…”
mentioning
confidence: 99%
“…A starting point is at the differentiation gene batteries that generate the biomineral matrix. Earlier evidence indicated that many specific protein components of the biomineral matrix are present in both demineralized embryonic skeletal spicules and demineralized adult endoskeleton, i.e., spines and test plates (9). Analysis of biomineralization genes in the S. purpuratus genome sequence (10) proves this is the case, although, for some families of these genes, certain paralogues are used in adult skeletons, some in embryonic and some in both.…”
mentioning
confidence: 99%
“…These proteins fall into two classes, those that are constituents of the skeletogenic matrix per se, that is, the protein armature of the spicule in which the calcite biomineral is embedded; and those that play other roles in the cellular process of skeletogenesis. The definition of skeletal matrix protein has rested on the painstaking biochemical isolation of spicule matrix components originally carried out by Wilt, Benson and their colleagues (Benson et al 1986;Killian & Wilt 1996). They have shown that even when cleaned of all external components the matrix consists of at least 50 different proteins, but unfortunately only a few of these are so far characterized.…”
Section: Introductionmentioning
confidence: 99%
“…A species-specific, invariant number of PMCs ingress into the blastocoel , and in Lytechinus spp., 64 PMCs ingress and extend filopodia to form a syncytium of two ventrolateral rings of cells. The PMCs deposit CaC03 and MgC03 crystals and spicule matrix proteins (Benson et al, 1986;Decker et al, 1987;Sucov et al, 1987;Livingston et al, 1991) from which a species-specific triradiate skeleton or spicule is formed.…”
mentioning
confidence: 99%